The Value of Local Wisdom in Lampung Community of Piil Pesenggiri “Sakai Sambayan” Towards the Climate Change Mitigation Policy - Oktasari, Ratih (Aksara: Jurnal Bahasa dan Sastra, 2025)
Climate change poses a critical global challenge that demands effective adaptation and mitigation strategies. This study examines the role of piil pesenggiri, with a focus on the sakai sambayan value, within the Lampung community’s cultural framework as it relates to climate change mitigation policies. Employing a qualitative, postcritical ethnographic approach, the research analyzes sakai sambayan as a form of cultural wisdom with implications for climate adaptation, using data from observations and interviews with community members in Margakaya Village, Pringsewu, Lampung. The findings reveal that sakai sambayan a locally grounded approach based on collective cooperation supports practical climate mitigation activities, especially in flood prevention, although these efforts are primarily driven by community initiative rather than formal policies. This research contributes to the field of anthropology by uncovering novel insights into how local wisdom informs public policy processes and implementation in climate change mitigation, underscoring the importance of integrating indigenous values in sustainable environmental governance.Keywords: piil pesenggiri, sakai sambayan, climate change policy